Logistics Analysis of the Supply Chain for Forest Biomass in Slovakia - Gejdoš Miloš; Hitka Miloš (Logi)
The demand for renewable energy sources and the construction of new consumer capacities for forest biomass, combined with increasing demands for nature protection and disturbances caused by global climate change, present several technological and logistical challenges. This study aims to analyze the main logistical problems in the production and transportation of forest biomass for energy use. The input data for the study were obtained from the databases of the National Forest Center and the Ministry of Agriculture and Rural Development. In the production cycle, harvesting operations related to forest management, including tending felling and main felling, were considered. Service prices were sourced from the public price lists of both private and state forest managers, as well as forestry machinery operators. Costs were calculated for three key points in the logistics flow: the skid way in the forest, the biomass supplier’s warehouse, and the heating plant utilizing the biomass. Our results indicate that, regardless of the production location or the age of the forest stand, the largest cost component is primarily the transportation of biomass to the point of consumption. After establishing the optimization structure, it is also necessary to ensure the operational functionality and continuous biomass supply.